Elaboración de un plan de prevención de riesgos laborales y salud ocupacional en el Taller de Gobierno Autónomo Descentralizado Municipal Sigchos. - Gallegos Jiménez, Héctor Geovanny (2018)
The present investigation work is oriented to elaborate a Plan of Prevention of Risks and Occupational Health in the Workshop of the Autonomous Decentralized Municipal Government of the Canton Sigchos, with the purpose of improving the security, health in the work realizing an analysis of the current situation in the workshop was found by means of tools and research techniques with indicators (tabulated results), the risks were identified through the matrix GTC-45 for the identification of the hazards and the evaluation of the risks in safety and health occupational, with this, carry out the preventive management through the following engineering controls: at the source, in the transmission medium, and in the worker with the support components, to mitigate the risks to which they are exposed, it is proposed and suggests: adequate signage according to current regulations; application of 9's; waste classification; verification and provision of Personal Protection Equipment according to the activity; training in safety and health for workers, as well as in the use and awareness of the E.P.P; emergency plan.